2018
DOI: 10.1186/s13046-018-0911-3
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma cell-secreted exosomal miR-155-5p induce proangiogenic switch of cancer-associated fibroblasts via SOCS1/JAK2/STAT3 signaling pathway

Abstract: BackgroundCancer-associated fibroblasts (CAFs) have been widely reported to promote tumor angiogenesis. However, the underlying mechanisms of the proangiogenic switch of CAFs remain poorly understood. This study aims to clarify the mechanisms underlying the proangiogenic switch of CAFs.MethodsNIH/3T3 cells were treated with B16 and B16F10-derived exosomes. Then the CAFs markers and proangiogenic factors were detected by RT-PCR and Western blot. CCK-8 assay, transwell migration assay, tube formation assay, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
184
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(191 citation statements)
references
References 37 publications
6
184
1
Order By: Relevance
“…Altered expression of miR‐155, miR‐21 and miR‐205 has been observed in various types of cancer . The results of the present study demonstrated that the levels of miR‐155 and miR‐21 were increased, whereas those of miR‐205 were decreased in the liver tissue of melanoma B16‐bearing mice at the premetastatic stage.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Altered expression of miR‐155, miR‐21 and miR‐205 has been observed in various types of cancer . The results of the present study demonstrated that the levels of miR‐155 and miR‐21 were increased, whereas those of miR‐205 were decreased in the liver tissue of melanoma B16‐bearing mice at the premetastatic stage.…”
Section: Discussionsupporting
confidence: 57%
“…The miR-155 molecule induces the proangiogenic switch of cancer-associated fibroblasts in melanoma; this microRNA downregulates suppressor of cytokine signalling 1, which leads to the activation of the JAK2/STAT3 signalling pathway and increases VEGFA, fibroblast growth factor 2 and matrix metallopeptidase 9 expression levels in cancer-associated fibroblasts. 23 MicroRNA miR-21 enhances oxidative stress and angiogenesis during melanoma development through modulation of the expression of critical target genes, such as forkhead Box O1, phosphatase and tensin homologue, hypoxia-inducible factor 1α and tissue inhibitor of metallopeptidase 3. 24 The molecule miR-205 acts as an oncosuppressor; this microRNA diminishes angiogenesis by targeting VEGFA and its downstream products.…”
mentioning
confidence: 99%
“…As a novel marker of CAFs, CAV1 was associated with metabolic reprogramming (18, 22, 39). In our previous study, tumoral EVs were capable tof inducing the transition of normal fibroblasts to CAFs (11, 40). In the present study, the up‐regulation of FAP and Tn‐c and down‐regulation of CAV1 suggest that TMV‐treated HGFs enable a phenotype switch to CAFs.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have demonstrated that salidroside inhibited JAK2/STAT3 signaling pathway in many cancers and downregulated MMP‐2 and MMP‐9 proteins . It has also been demonstrated that MMP‐2 and MMP‐9 are associated with the JAK2/STAT3 signaling pathway . MMP2 and MMP9 are important effector molecules in JAK2/STAT3 pathway, and activation of JAK2/STAT3 can increase expression of MMP2 and MMP9, resulting in degradation of extracellular matrix .…”
Section: Resultsmentioning
confidence: 99%